The Alcobaça Abbey hydraulic landscape - Mascarenhas, José Manuel de (2017)
Introduction: This paper concerns the main domain (“coutos”) of Alcobaça Abbey (central Portugal), founded in 1153. It shows the involvement of the Cistercian monks in shaping hydraulic landscapes along time. This monastic territory is limited westwards by the Atlantic ocean with a cliff coast indented by two large gulfs, the Pederneira lagoon, north , totally sanded up nowadays, and the Alfeizerão lagoon, south, of which only the São Martinho bay still exists. These landscapes have been consolidated along with the monks’ intervention in the hydrographic plan, particularly through a network of canals, the types of which can be summarized as follows: - canals for water conveyance and evacuation, to and from the abbey buildings; - canals related with water-powered engines as grain-, oil-, saw- and fulling-mills, forges and other industrial devices; - canals consequent to the diversion of rivers and streams with two main purposes: . to drain the fields in order to improve the marshes for agricultural use; . to irrigate cultures. Method: The hydraulic landscape planning has been identified and characterized through documentary research, stereoscopic interpretation of panchromatic and infrared “false colour” vertical aerial photographs, and land surveys. Findings / discussion: Flood control seems to have been one of the main hydro technical concern of the Cistercians. Their strategy was to subdivide some hydrographic basins, so that the fields would not be flooded. This was observed in the fields of the ancient Pederneira lagoon, for which an important cartography is available. But the same strategy was probably applied in the Alfeizerão fields. Besides the canals which were analyzed, other canal networks existed but it has not been possible to identify them till now because of the soil erosion or the topographic transformations together with the documental lack of knowledge. The more blatant situation concerns the old Valdeventos monastic farm, at the eastern limit of the “coutos”, where was found a large water storage structure, a tank, presumably to supply an irrigation canal network. Conclusion: Between the early 12th century and the mid 18th century, the Cistercian monks of the Alcobaça Abbey conceived and set in their “coutos” a hydraulic landscape composed by a network of canals with different purposes, and other water devices. This waterscape presents a high heritage value and deserves to be protected and developed.